Long-term Effects of Calcium β-Hydroxy-β-Methylbutyrate and Vitamin D3 Supplementation on Muscular Function in Older Adults With and Without Resistance Training: A Randomized, Double-blind, Controlled Study. (28th August 2020) - Rathmacher, John A; Pitchford, Lisa M; Khoo, Paul; Angus, Hector; Lang, James; Lowry, Kristin; Ruby, Carol; Krajek, Alex C; Fuller, John C; Sharp, Rick L
Abstract: The primary aim of this study was to determine whether supplementation with calcium β-hydroxy-β-methylbutyrate (HMB) and vitamin D3 (D) would enhance muscle function and strength in older adults. Older adults over 60 years of age with insufficient circulating 25-hydroxy-vitamin D (25OH-D) levels were enrolled in a double-blinded controlled 12-month study. Study participants were randomly assigned to treatments consisting of: (a) Control + no exercise, (b) HMB+D + no exercise, (c) Control + exercise, and (d) HMB+D + exercise. The study evaluated 117 participants via multiple measurements over the 12 months that included body composition, strength, functionality, and questionnaires. HMB+D had a significant benefit on lean body mass within the nonexercise group at 6 months (0.44 ± 0.27 kg, HMB+D vs −0.33 ± 0.28 kg, control, p < .05). In nonexercisers, improvement in knee extension peak torque (60°/s) was significantly greater in HMB+D-supplemented participants than in the nonsupplemented group ( p = .04) at 3 months, 10.9 ± 5.7 Nm and −5.2 ± 5.9 Nm, respectively. A composite functional index, integrating changes in handgrip, Get Up, and Get Up and Go measurements, was developed. HMB+D + no exercise resulted in significant increases in the functional index compared with those observed in the control + no exercise group at 3 ( p = .03), 6 ( p = .04), and 12 months ( p = .04). Supplementation with HMB+D did not further improve the functional index within the exercising group. This study demonstrated the potential of HMB and vitamin D3 supplementation to enhance muscle strength and physical functionality in older adults, even in individuals not engaged in an exercise training program.